Prevalence of Hepatitis B Surface Antigen, Human Immunodeficiency Virus and Malaria among Pregnant Women Attending Antenatal Clinic at Eku Baptist Government Hospital, Eku, Delta State, Nigeria. - Akpo, C.O. *, Edonmi, T. J and Okoye, L. C. (Sokoto Journal of Medical Laboratory Science)
Hepatitis B, Human Immunodeficiency Virus/ Acquired Immunodeficiency Syndrome and malaria are global threats to public health because of their prevalence and tendency to affect offspring when transmitted vertically. The aim of this study was to determine the prevalence of hepatitis B (HBsAg), HIV and malaria among antenatal women in Eku Baptist Government Hospital, Delta State, Nigeria. A questionnaire was administered to each voluntary participant to obtain information on their socio-demographic characteristics. The presence of HBsAg, and HIV were determined from the serum sample of each study subject using SD Bioline HBsAg serological kit and ABON-HIV TM 1/2/0 Tri-line Human Immunodeficiency Virus Rapid Test Device respectively. The presence of malaria was determined using whole blood from each study subject by rapid diagnostic testing and further confirmed using microscopic technique. A total of 100 samples were tested and the prevalence of malaria, HBsAg and HIV among the pregnant women were 23%, 7% and 2% respectively. The HBsAg/malaria co-infection prevalence rate was 2%. There was no HBsAg/HIV and HIV/malaria co-infection. Age group 25-30 years had highest prevalence 2(5.4%) and 10 (27%) for HIV and malaria respectively while the age group 31-35 years had the highest prevalence 4(13.8%) for HBsAg. The age group 43-49 years tested negative to all three infections. The prevalence of hepatitis B, HIV and malaria is still a challenge in Eku and surrounding towns. This report calls urgently for effective health interventions and health education at the national and state levels on prevention of mother-to-child transmission of HBV and HIV. Malaria should be addressed by incorporating regular periodic prophylaxis for women attending antenatal clinics to resolve asymptomatic infections and save the lives of the women.